1997
DOI: 10.1016/s0741-5214(97)70209-x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous closure of selected iatrogenic pseudoaneurysms and arteriovenous fistulae

Abstract: The natural history of stable pseudoaneurysms and arteriovenous fistulae is benign and frequently results in spontaneous resolution, which allows properly selected patients to be managed without operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
133
0
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(141 citation statements)
references
References 28 publications
2
133
0
6
Order By: Relevance
“…Pseudoaneurysms usually occur when an arterial puncture site does not adequately seal. A previous study indicated that pseudoaneurysms thrombosed spontaneously in 88% of the cases when pseudoaneurysms were <30 mm [2]. Therefore, in general, observation of small pseudoaneurysms is thought to be reasonable in the absence of severe pain, such as this case.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Pseudoaneurysms usually occur when an arterial puncture site does not adequately seal. A previous study indicated that pseudoaneurysms thrombosed spontaneously in 88% of the cases when pseudoaneurysms were <30 mm [2]. Therefore, in general, observation of small pseudoaneurysms is thought to be reasonable in the absence of severe pain, such as this case.…”
Section: Discussionmentioning
confidence: 60%
“…In general, pseudoaneurysms are thought to be thrombosed spontaneously. A previous study reported that spontaneous thrombosis of pseudoaneurysm occurred in 88% of cases with small pseudoaneurysms at a mean of 23 days [2]. Another prospective study described that failure of thrombosis was associated with pseudoaneurysms >18 mm and the concomitant use of anticoagulation or antiplatelet agents [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small pseudoaneurysms, especially those with diameters smaller than 2.0 cm, can be treated conservatively and spontaneous thrombosis can be expected 16,17 . Compression guided by ultrasound is a treatment that has variable results and success rates of 50 to 95% and also causes patients discomfort 18 .…”
Section: Discussionmentioning
confidence: 99%
“…7 Femoral arteriovenous fistulae are also described following percutaneous femoral arterial catheterization. 8 To our knowledge, this is the first report of arteriovenous fistula formation after peripheral venous catheterization for allogeneic peripheral blood progenitor cell collection. It is notable that establishing venous access was neither difficult nor traumatic in this donor.…”
mentioning
confidence: 81%